Analysis of the expression and activity of nitric oxide synthase from marine photosynthetic microorganisms - Foresi, Noelia Pamela (2016)
Nitric oxide (NO) functions as a signaling molecule in many biological processes in species belonging to all kingdoms of life. In animal cells, NO is synthesized primarily by NO synthase (NOS), an enzyme that catalyze the NADPH-dependent oxidation of l -arginine to NO and l -citrulline. Three NOS isoforms have been identifi ed, the constitutive neuronal NOS (nNOS) and endothelial NOS (eNOS) and one inducible (iNOS). Plant NO synthesis is complex and is a matter of ongoing investigation and debate. Despite evidence of an Arg-dependent pathway for NO synthesis in plants, no plant NOS homologs to animal forms have been identifi ed to date. In plants, there is also evidence for a nitrate-dependent mechanism of NO synthesis, catalyzed by cytosolic nitrate reductase. The existence of a NOS enzyme in the plant kingdom, from the tiny single-celled green alga Ostreococcus tauri was reported in 2010. O. tauri shares a common ancestor with higher plants and is considered to be part of an early diverging class within the green plant lineage. In this chapter we describe detailed protocols to study the expression and characterization of the enzymatic activity of NOS from O. tauri. The most used methods for the characterization of a canonical NOS are the analysis of spectral properties of the oxyferrous complex in the heme domain, the oxyhemoglobin (oxyHb) and citrulline assays and the NADPH oxidation for in vitro analysis of its activity or the use of fl uorescent probes and Griess assay for in vivo NO determination. We further discuss the advantages and drawbacks of each method. Finally, we remark factors associated to the measurement of NOS activity in photosynthetic organisms that can generate misunderstandings in the interpretation of results.